Unbalanced upregulation of ryanodine receptor 2 plays a particular role in early development of daunorubicin cardiomyopathy - Kucerova, Dana; Doka, Gabriel; Kruzliak, Peter; Turcekova, Katarina; Kmecova, Jana; Brnoliakova, Zuzana; Kyselovic, Jan; Kirchhefer, Uwe; Müller, Frank U; Krenek, Peter; Boknik, Peter; Klimas, Jan (American journal of translational research, 2015)
Calcium release channel on the sarcoplasmic reticulum of cardiomyocytes (ryanodine receptor type 2, RyR2) plays a critical role in the regulation of calcium and was identified as a crucial factor for development of chronic anthracycline cardiomyopathy. Its early stages are less well described although these determine the later development. Hence, we tested the effect of repeated, short-term anthracycline (daunorubicin) administration on cardiac performance, cardiomyocyte function and accompanied changes in calcium regulating proteins expression. Ten-twelve weeks old male Wistar rats were administered with 6 doses of daunorubicin (DAU, 3 mg/kg, i.p., every 48 h), controls (CON) received vehicle. Left ventricular function (left ventricular pressure, LVP; rate of pressure development, +dP/dt and decline, -dP/dt) was measured using left ventricular catheterization under tribromethanol anaesthesia (15 ml/kg b.w.). Cell shortening was measured in enzymatically isolated cardiomyocytes. The expressions of RyR2 and associated intracellular calcium regulating proteins, cytoskeletal proteins (alpha-actinin, alpha-tubul in) as well as oxidative stress regulating enzymes (gp91phox, MnSOD) were detected in ventricular tissue samples using immunoblotting. mRNA expressions of cardiac damage markers (Nppa and Nppb, atrial and brain natriuretic peptides; Myh6, Myh7 and Myh7b, myosin heavy chain alpha and beta) were detected using RT-PCR. Thiobarbituric acid reactive substances concentration was measured to estimate oxidative stress. DAU rats exhibited significantly depressed left ventricular features (LVP by 14%, +dP/dt by 36% and -dP/dt by 30%; for all P<0.05), in line with concomitant increase in Nppa and Nppb gene expressions (3.23- and 2.18-fold, for both P<0.05), and a 4.34-fold increase in Myh7 (P<0.05). Controversially, we observed increased cell shortening of isolated cardiac cells by 31% (p<0.05). DAU administration was associated with a twofold upregulation of RyR2 (P<0.05), but not of other examined Ca(2+) regulating proteins remained. In addition, we observed a significant reduction in alpha-tubulin (by 46% when compared to CON P<0.05). Indicators of oxidative injury were unaffected. In conclusion, unbalanced RyR2 overexpression plays a particular role in early development of daunorubicin cardiomyopathy characterized by discrepant in situ versus in vitro cardiac performance.
Keywords: oxidative stress; daunorubicin cardiomyopathy; Calcium; ryanodine receptor 2 (RyR2)